1998
DOI: 10.1002/(sici)1097-0193(1998)6:5/6<383::aid-hbm10>3.3.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

ERP and fMRI measures of visual spatial selective attention

Abstract: In two prior studies, we investigated the neural mechanisms of spatial attention using a combined event-related potential (ERP) and positron emission tomography (PET) approach (Heinze et al. [1994]: Nature 392:543-546; Mangun et al. [1997]: Hum Brain Mapp 5:273-279). Neural activations in extrastriate cortex were observed in the PET measures for attended stimuli, and these effects were related to attentional modulations in the ERPs at specific latencies. The present study used functional magnetic resonance ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
1
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 0 publications
7
74
1
3
Order By: Relevance
“…In particular, if the benefits of SSRIs relate to the core deficits of autism, as seems to be the case clinically, this would strongly support the equivalency of some forms of autism with major psychiatric disorders. An important aspect of this concept is the recognition of high-functioning autism, in particular, as a disorder primarily of left-hemisphere language and semantic/contextual function, with preservation of functions (mainly visuospatial skills and veridical rote memory) associated with the right hemisphere (Mangun et al 1998). Such a pattern of disturbance would correspond to the low left-hemisphere serotonin found with C 11 -AMT PET scans in young boys with autism (Chugani et al 1997, DeLong 1999.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, if the benefits of SSRIs relate to the core deficits of autism, as seems to be the case clinically, this would strongly support the equivalency of some forms of autism with major psychiatric disorders. An important aspect of this concept is the recognition of high-functioning autism, in particular, as a disorder primarily of left-hemisphere language and semantic/contextual function, with preservation of functions (mainly visuospatial skills and veridical rote memory) associated with the right hemisphere (Mangun et al 1998). Such a pattern of disturbance would correspond to the low left-hemisphere serotonin found with C 11 -AMT PET scans in young boys with autism (Chugani et al 1997, DeLong 1999.…”
Section: Discussionmentioning
confidence: 99%
“…The visual module was previously assumed to correspond to activity in the fusiform gyrus, but actually seems to respond better to activity in the middle occipital gyrus, at least for the five tasks that we analyzed. The middle occipital gyrus is typically involved in visual-spatial attention (22,35). Given that the visual regressor that we used corresponds to attending objects, this seems to be a sensible match.…”
Section: Auralmentioning
confidence: 99%
“…However, we still lack a detailed retinotopic map of later components, which are more commonly studied in the ERP literature, such as P1 and N1 (Di Russo et al, 2012;Klimesch, 2011;Mangun et al, 1998). For instance, it has recently been demonstrated that the amplitude of some components such as P1 or the face-sensitive N170 is modulated by the gaze fixation position within a face (Zerouali et al, 2013).…”
Section: Introductionmentioning
confidence: 99%